2018
DOI: 10.1891/1078-4535.24.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Spiritually Based Care through Gratitude Practices: A Health-Care Improvement Project

Abstract: Interactive educational sessions on spirituality can improve a health-care team's attitudes, comfort level, and practice of providing spiritually based care. Generalizability is limited to the project site, but the process could be implemented in other facilities to determine if similar results can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Prior studies from other countries showed that the objectivity of the effect measurement of spiritual nursing education increased after providing spiritual nursing education for nurses [ 43 ]. One study objectified the effect of spiritual nursing education by examining the number of spiritual nursing interventions before and after spiritual nursing education [ 44 ]. For objective evaluation, evaluation checklists, in which the evaluation criteria are objectively presented not only for self-evaluation, can be used for head nurses or patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies from other countries showed that the objectivity of the effect measurement of spiritual nursing education increased after providing spiritual nursing education for nurses [ 43 ]. One study objectified the effect of spiritual nursing education by examining the number of spiritual nursing interventions before and after spiritual nursing education [ 44 ]. For objective evaluation, evaluation checklists, in which the evaluation criteria are objectively presented not only for self-evaluation, can be used for head nurses or patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the chronic nature of the diseases and the complex psychosocial factors of PsO and RA, nonpharmacologic therapies, such as biopsychosocial intervention, might be used as a complementary treatment strategy [ 7 , 8 , 9 , 10 , 11 ]. Indeed, several nonpharmacological non-invasive therapies, including mind–body interventions, have become available for chronic medical conditions in recent years [ 12 , 13 , 14 , 15 ]. Mind–body interventions are often part of the multidisciplinary rehabilitation and incorporate strategies that are thought to improve psychological and physical well-being, aiming to allow patients to take an active role in their treatment and promote people’s ability to cope with their condition and improve HR-QoL [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%